HYPOTHYROIDISM ASSOCIATED HYPOKALEMIA PERIODIC PARALYSIS - Min, Sophanara; Sor, Hokban; Sieng, Lundy; Sorl, Sung; Seang, Sokkhorn (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 29-year-old female, recently delivered a baby girl, present with recurrent attacks of acute weakness in all 4 limbs. The patient had a history of hyperthyroidism during the 3rd trimester of her pregnancy in 2022. She didn't receive treatment for hypothyroidism at that time. On examination, the patient had quadriparesis with hypotonia, diminished deep tendon reflexes, delayed relaxation of ankle jerks and flexor plantar response, and prominent muscle weakness in both legs. She had normal mental function without any cranial nerve, sensory, or sphincter involvement. The blood test showed hypokalemia at 1.8mmol/l, T4: 4.11 pmol/l, T3: 2.93 pmol/l, TSH: >100 mUI, anti-TPO: 191.3 UI/ml, anti-Tg: 557 UI/ml and 24-hr urine K: 25 mmol/24 h. The patient was treated with: KCl 3 g by syringe pump in 5 ml/H, kaleorid 600 mg 6 cp, and levothyroxine 75 ug. Recurrent hypokalemic paralysis is an extremely unusual presentation of hypothyroidism. To the best of our knowledge, this is the fourth reported case of hypothyroidism associated with recurrent hypokalemic paralysis.